Prognostic role of IL-4, IL-2 and TLR-2 for predicting of course of food allergy in children - Pakholchuk, O. P.; Пахольчук, Ольга Петрівна (publishing center of the ESCBM, The Czech Republic, 2018)
Food allergy (FA) is considered as one of the main health problems of early childhood and is considered as the first step of “atopy march”. It was proved, that important role in further development of allergic diseases has IL-4. Promising positive results of target therapy of atopic dermatitis with anti-IL-4 antibodies underline importance of this signaling protein. The aim of the study was to evaluate possible prognostic role of IL-4 for predicting of the long-term effects of the correction of barrier dysfunction in children with food allergy in comparison with IL-2 and TLR-2.
Keywords: тези доповідей; food allergy; IL-4; epidermal barrier; treatment; emollient